Recombinant human growth hormone and insulin-like growth factor-1 do not affect mitochondrial derived highly reactive oxygen species production in peripheral blood mononuclear cells under conditions of substrate saturation in-vitro. Issue 1 (December 2016) - Keane, James; Tajouri, Lotti; Gray, Bon
Abstract Background The purpose of this study was to investigate the mitochondrial effects exerted by physiological and supra-physiological concentrations of recombinant human growth hormone (rhGH) and recombinant insulin-like growth factor-1 (rIGF-1) under conditions of substrate saturation in peripheral blood mononuclear cells (PBMCs). Methods PBMCs from healthy male subjects were treated with either rhGH, at concentrations of 0.5, 5 and 50 μg/L, or rIGF-1 at concentrations of 100, 300 and 500 μg/L for 4 h. Mitochondrial membrane potential (Δψm ) and mitochondrial levels of highly reactive oxygen species (hROS) were subsequently analysed. This analysis was performed by flow cytometry in digitonin permeabilized cells, following treatment with saturating concentrations of various respiratory substrate combinations and the use of specific electron transport chain (ETC.) complex inhibitors, enabling control over both the sites of electron entry into the ETC. at complexes I and II and the entry of electrons from reduced carriers involved in β-oxidation at the level of ubiquinol. Results Neither rhGH nor rIGF-1 exerted any significant effect on Δψm or the rate of hROS production in either lymphocyte or monocyte sub-populations under any of the respiratory conditions analysed. Conclusion That neither hormone was capable of attenuating levels of oxidative stress mediated via either complex I linked respiration or lipid-derived respiration could have serious health implications for the use of rhGH in healthy individuals, which is frequently associated with significant increases in the bioavailability of free fatty acids (FFA). Such elevated supplies of lipid-derived substrates to the mitochondria could lead to oxidative damage which would negatively impact mitochondrial function.